(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research discusses the importance of supply chain risk management (SCRM) in the context of increasingly complex and interconnected global supply chains. With increased vulnerability to disruption, as seen during the COVID-19 pandemic, companies need to develop robust SCRM strategies to ensure continuity of operations. This research aims to identify common and emerging risks in the supply chain, analyze factors that influence the severity of risks, and explore effective mitigation strategies. Through a systematic literature review approach, this research finds that traditional risks such as operational disruption and price fluctuations are still a major concern, while new risks such as cyber attacks and geopolitical instability are increasingly dominating. Additionally, factors such as supply chain complexity, reliance on technology, and market dynamics play an important role in determining the impact of risks. This research suggests that companies adopt strategies of supplier diversification, digitalization, collaboration with stakeholders, and sustainable practices to increase the resilience of their supply chains.